Alexis in America : A Russian Grand Duke's Tour, 1871-1872 - Farrow, Lee A., 1966- (Book collections on Project MUSE., 2014)
In the autumn of 1871, Alexis Romanov, the fourth son of Tsar Alexander II of Russia, set sail from his homeland for an extended journey through the United States and Canada. A major milestone in U.S.-Russia relations, the tour also served Duke Alexis's family by helping to extricate him from an unsuitable romantic entanglement with the daughter of a poet. Alexis in America recounts the duke's progress through the major American cities, detailing his meetings with celebrated figures such as Samuel Morse and Henry Wadsworth Longfellow and describing the national self-reflection that his presenc.